IMPLEMENTASI ISLAMIC GOOD CORPORATE GOVERNANCE DALAM PENGELOLAAN ZIS DI BAZNAS KABUPATEN GRESIK (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2024)
ABSTRACT Islamic economic principles-based financial instruments, Zakat, Infak, Sedekah (ZIS), play a key role in supporting social and economic development of the community. The fundamental principles of Islamic economics in ZIS create a foundation for a just and sustainable life. Challenges in transactions include a lack of understanding related to ZIS, a perception of a simple concept, and low trust of muzakki in the zakat institution. Effective governance is needed to establish a professional and trusted zakat institution. Islamic Good Corporate Governance (IGCG), a governance guideline based on Islamic law, reinforces the principles of zakat management according to Law No. 23 of 2011 Article 2. The objective of this research is to identify IGCG indicators in BAZNAS Gresik and analyze their implementation in managing ZIS funds. The research results indicate that BAZNAS Gresik consistently applies the principles of Islamic Good Corporate Governance (IGCG) in zakat fund management. Through principles of transparency, accountability, responsibility, independence, and fairness, BAZNAS Gresik successfully builds trust within the community and provides positive impact for mustahik. Concrete steps such as the use of technology, employee training, regular reporting, and productive zakat programs demonstrate the commitment of BAZNAS Gresik in creating sustainability and social justice. Key Words: BAZNAS Gresik, Islamic Good Corporate Governance (IGCG), Zakat, Infak, Sedekah (ZIS). ABSTRAK Instrumen keuangan berbasis prinsip ekonomi Islam, Zakat, Infak, Sedekah (ZIS), memainkan peran kunci dalam mendukung pembangunan sosial dan ekonomi masyarakat. Prinsip dasar ekonomi Islam dalam ZIS menciptakan fondasi kehidupan yang adil dan berkelanjutan. Tantangan perzakatan mencakup kurangnya pemahaman terkait ZIS, persepsi konsep yang sederhana, dan rendahnya kepercayaan muzakki terhadap lembaga amil zakat. Tata kelola efektif diperlukan untuk menciptakan lembaga amil zakat yang profesional dan dipercayai masyarakat. Islamic Good Corporate Governance (IGCG), pedoman tata kelola berdasarkan syariah Islam, memperkuat prinsip-prinsip pengelolaan zakat sesuai UU No. 23 Tahun 2011 Pasal 2. Tujuan penelitian ini mengidentifikasi indikator IGCG di BAZNAS Kabupaten Gresik dan menganalisis implementasinya dalam pengelolaan dana ZIS. Hasil penelitian menunjukkan bahwa BAZNAS Gresik secara konsisten menerapkan prinsip-prinsip Islamic Good Corporate Governance (IGCG) dalam pengelolaan dana zakat. Dengan prinsip transparency, accountability, responsibility, independence, and fairness, BAZNAS Gresik berhasil membangun kepercayaan masyarakat dan memberikan dampak positif bagi mustahik. Langkah-langkah konkret seperti penggunaan teknologi, pelatihan karyawan, pelaporan rutin, dan program zakat produktif menunjukkan komitmen BAZNAS Gresik dalam menciptakan keberlanjutan dan keadilan sosial. Kata Kunci: BAZNAS Gresik, Islamic Good Corporate Governance (IGCG), Zakat, Infak, Sedekah (ZIS)